The Concept of Healing Waterscapes in Public Open Spaces to Construct the Positive Psychology of Visitors - Prasandya, Km Deddy Endra; Satria, Made Wina; Adiartha, Made Arya (Jurnal Koridor, 2024)
Public open spaces contain various features that have psychological effects on human mental health. Water, as one of the key elements in landscape design, not only enhances aesthetics but also provides sensory stimulation, social interaction, and psychological benefits. It possesses therapeutic qualities that promote relaxation and reduce stress. Given the rising prevalence of mental health issues among adolescents in Bali, public open spaces incorporating waterscapes play a crucial role. The concept of a "healing waterscape" can be applied in such spaces, where environmental elements are strategically designed to improve mental well-being through psychological approaches. However, no clear criteria for healing waterscape design have been formulated, and it remains unclear whether such criteria are being applied in the waterscapes of public open spaces in Denpasar City and Klungkung Regency. This study aims to establish criteria for healing waterscape design in public open spaces and assess the extent to which these criteria are implemented in Denpasar City and Klungkung Regency. Using a mixed-methods data analysis with JMP software, the study identifies four key variables in healing waterscape design: social, behavioral, cognitive, and emotional factors. The design criteria that should be considered for public space waterscapes in Denpasar and Klungkung include activity diversity, site characteristics, spatial variety, acoustics, water shape, movement, flow, lighting and signage, and both biotic and abiotic components.